Association of sleep behaviors, insulin resistance surrogates, and the risk of hypertension in Chinese adults with type 2 diabetes mellitus - Yao, Xuelin; Lu, Fangting; Wang, Zhen; Miao, Yahu; Feng, Qing; Zhang, Yi; Jiang, Tian; Tang, Songtao; Zhang, Nan; Dai, Fang; Hu, Honglin; Zhang, Qiu (Frontiers in Endocrinology, 2023)
Objective: To evaluate the association between midday napping, combined sleep quality, and insulin resistance surrogates, and the risk of hypertension in patients with type 2 diabetes mellitus (T2DM).Methods: Data were collected using a standardized questionnaire. Binary logistic regression was performed to estimate the odds ratio (OR) and 95% confidence interval (CI) for risk of hypertension. Systolic and diastolic blood pressure were grouped as categorical variables, and unpaired two-sided Student's t-test and Spearman correlation analysis were performed to estimate the association between different blood pressure levels and insulin resistance surrogates.